Reductive sulfinylation by nucleophilic chain isomerization of sulfonylpyridinium - Yifan Li; Weigang Zhang; Jeonguk Kweon; Yi Pan; Qing Wang; Sukbok Chang; Yi Wang (Nature Communications)
Abstract Sulfur-containing units are fundamental components widely found in bioactive compounds, prompting notable efforts toward developing synthetic methodologies for incorporating sulfur functionality into organic precursors. The synthesis of sulfinate esters and sulfinamides has garnered significant interest owing to their immense potential for applications, especially in drug development. However, most existing synthetic protocols suffer from some limitations. To address these challenges, we herein present a practical and efficient approach for the reductive sulfinylation of diverse nucleophiles with sulfonylpyridinium salts (SulPy) through the nucleophilic chain substitution, namely SNC reaction, which involves S(VI) to S(IV) nucleophilic chain isomerization process. These versatile sulfinylation reagents can be readily accessed from diverse commercially available resourses. The late-stage modification of complex molecules and the ability to rapidly synthesize numerous sulfinyl bioisosteres of various drugs highlights the utility of this protocol.